Psychological and Environmental Correlates of Moderate-to-Vigorous Physical Activity and Step Counts Among Older Adults With Cognitive Decline. Issue 4 (August 2019) - Harada, Kazuhiro; Lee, Sangyoon; Lee, Sungchul; Bae, Seongryu; Harada, Kenji; Suzuki, Takao; Shimada, Hiroyuki
Promoting physical activity (PA) among older adults with cognitive decline is important for maintaining and improving their health. Identifying psychological and environmental PA correlates in this population can help develop effective strategies for PA promotion. Since past findings with healthy older adults may not generalize to those with cognitive decline, this study offers data on how self-efficacy, self-regulation, and social-environmental factors were associated with PA among a group of older adults with cognitive decline. We report secondary analysis of baseline data from a randomized control study of 262 older participants ( M  = 76.2 years) who showed a decline in global cognitive function as defined by Mini-Mental State Examination scores between 21 and 24. The participants' PA was measured by an accelerometer, and participants completed questionnaires measuring self-efficacy, self-regulation, social support, social network, and demographic variables. In this study, we evaluated the participants' neighborhood environment with a geographic information system and found through stepwise multiple regression analyses that self-efficacy, gender, and age were associated with PA variables, while self-regulation and environmental factors were not. Thus, perceived self-efficacy was an important psychological correlate of PA in this group of older adults with cognitive decline. PA promotion interventions for this population should attend to self-efficacy, gender, and age.